Governance Through Social Learning - Paquet, Gilles (Governance Series, 1999)
Governance connotes the way an organization, an economy, or a social system co-ordinates and steers itself. Some insist that governing is strictly a top-down process guided by authority and coercion, while others emphasize that it emerges bottom-up through the workings of the free market. This book rejects these simplistic views in favour of a more distributed view of governance based on a mix of coercion, quid pro quo market exchange and reciprocity, on a division of labour among the private, public, and civic sectors, and on the co-evolution of these different integration mechanisms. This book is for both practitioners confronted with governance issues and for citizens trying to make sense of the world around them.